No Survival Effect in Cell Lines with Different Growth Factor-Induced Division Rates, but with Different Fractionation Schemes - Lena Blanke; Laura S. Hildebrand; Rainer Fietkau; Luitpold Distel (Radiation)
The aim of this work was to investigate the relationship between the growth rate of tumor cells and their fractionation gain. Two head and neck squamous cell carcinoma (HNSCC) cell lines, one human papillomavirus (HPV) negative (HPV−) and one HPV+, and a primary fibroblast cell line were supplemented with four different concentrations of fetal bovine serum (FBS) to achieve different division rates. The effect of five different fractionation regimens was studied, namely 1 × 10 Gy, 2 × 5 Gy, 3 × 3.3 Gy, 4 × 2.5 Gy, and 5 × 2 Gy. Survival was studied using the colony-forming assay. Different concentrations of FBS were used to achieve different doubling rates for all cell lines. The HPV+ cell line was significantly more sensitive to radiation than the HPV− cell line in all fractionation schemes. The fibroblast cell line was less sensitive at low fractionation compared to the tumor cell lines. Low fractionation had a significantly higher effect, except for 5 × 2 Gy fractionation, which had a higher effect than 4 × 2.5 Gy. The number of radiosensitive mitoses during irradiation in the fractionation scheme could not explain the higher effect of 5 × 2 Gy. There was no difference in survival with the four different concentrations of FBS in all three cell lines and different fractionations. The doubling time (DT) rates of cell lines resulting from FBS deprivation do not reflect the expected increased radiation sensitivity of rapidly dividing cells.